2015
DOI: 10.3923/aje.2015.64.71
|View full text |Cite
|
Sign up to set email alerts
|

Study of Latent Toxoplasma gondii Role in Level of Testosterone, DHEA, Cortisol and Prolactin Hormones of Young Persons

Abstract: Toxoplasmosis influences the behavior and personality of infected persons. Possible mechanisms for these psychic disorders include its effect on dopamine and on hormone levels. In the present research, the effect of latent toxoplasmosis on testosterone, DHEA, cortisol and prolactin hormones in the infected and noninfected individuals was examined. A total of 215 plasma sample were examined for IgG and IgM anti-Toxoplasma antibody, testosterone, DHEA, cortisol and prolactin levels. In addition the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In males, 9 studies reported an increased level of testosterone in T . gondii seropositive individuals compared to seronegative counterparts [ 29 , 30 , 32 , 33 , 38 41 , 43 ]. As such, in females, seven studies reported elevated levels of testosterone in T .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In males, 9 studies reported an increased level of testosterone in T . gondii seropositive individuals compared to seronegative counterparts [ 29 , 30 , 32 , 33 , 38 41 , 43 ]. As such, in females, seven studies reported elevated levels of testosterone in T .…”
Section: Resultsmentioning
confidence: 99%
“…As such, in females, seven studies reported elevated levels of testosterone in T . gondii seropositive than seronegative counterparts [ 29 , 30 , 32 , 34 , 37 – 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations